Comparison of endoscopic and microscopic microvascular decompression for treating primary trigeminal neuralgia - Li, Lei; Shao, Dongqi; Zheng, Xialin; Pan, Yuanbo; Sun, Tao; Tang, Huadong; Zhai, Hongjie; Dong, Xiaohui; Sun, Jing; Fang, Mengtian; Lou, Feiyun; Jiang, Zhiquan (Frontiers in Neurology, 2025)
ObjectiveTo compare the intraoperative outcome and postoperative efficacy of endoscopic and microscopic microvascular decompression (MVD) under neuroelectrophysiological monitoring in the treatment of primary trigeminal neuralgia (PTN).MethodsThis retrospective study included 131 patients with PTN who were admitted to our hospital between January 2019 and October 2022. The patients were categorized according to the treatment received into the endoscopic group (n = 53) (endoscopic MVD) and the microscopic group (n = 78) (microscopic MVD). All patients were treated under neuroelectrophysiological monitoring. The surgical time, identification of offending vessels, full exposure of trigeminal nerve (TN) structure, the rate of one-time decompression, postoperative efficacy, complications, postoperative hospital stay and recurrence rate were compared between both groups.ResultsThere were differences in incision length and bone flap diameter between the two groups (p < 0.05). Endoscopy was more minimally invasive compared to microscopy; however, there was no significant difference in total surgical time and blood loss between the two groups (p > 0.05). In the group with no neurovascular compression identified during preoperative assessment, the surgical duration was significantly shorter with endoscopy compared to microscopy (p < 0.05), which indicated that endoscopic treatment has a time advantage in this condition. The consistency rate of preoperative magnetic resonance angiography (MRA) result and intraoperative offending vessels differed between the two groups (p < 0.05), indicating that endoscopy may be more accurate than microscopy in detecting offending vessels. Compared to microscopes, endoscopes provide a higher rate of full exposure of the TN (p < 0.05). This difference is primarily observed in cases where there is obstruction by the petrosal protuberance tubercle (PPT) or petrosal vein (PV). Additionally, endoscopes offer a higher rate of one-time decompression which means that the need to adjust the Teflon pledget is less frequent (p < 0.05), thereby reducing the number of nerve disturbances. There was no significant difference in postoperative remission rate and Barrow Neurological Institute Pain Intensity Score (BNI score) between the groups (p > 0.05). Compared to the microscopy group, the recurrence rate at 2 years and the last follow-up after endoscopic surgery was lower; however, the difference was not significant (p > 0.05). There was no significant difference in the incidence of postoperative complications, mortality rate, and length of hospital stay between the groups (p > 0.05).ConclusionEndoscopic and microscopic MVD are effective for PTN and have comparable outcomes. Endoscopy enhances visualization and identification of offending vessels; moreover, compared with microscopy, endoscopy is more minimally invasive and suitable for detecting and fully separating potentially hidden offending vessels; however, its technical complexity necessitates individualized treatment based on patient needs and institutional expertise.